Judicial Review of State-Owned Enterprises at the Crossroads - Chen, Mai (Victoria University of Wellington Law Review, 1994)
This article determines the impact of the Court of Appeal decision Auckland Electric Power Board v Electricity Corporation of New Zealand on the scope of judicial review under the Judicature Amendment Act 1972, and specifically, on judicial review of the commercial decisions of State-owned enterprises. It asks why these judges differ in their approach to the scope of judicial review from those in other cases. The article then compares the approach under judicial review in this case with that under the New Zealand Bill of Rights Act 1990 in Federated Farmers of NZ (Inc) v NZ Post Ltd, and concludes that the New Zealand Bill of Rights Act can be used to subject the decisions of corporatised, and maybe also privatised, bodies to substantive review akin to economic regulation. It determines whether this is appropriate. The article concludes by asking whether the appeal of the ECNZ decision to the Privy Council in early 1994 could be made under section 27(1) of the New Zealand Bill of Rights Act for failure to grant "natural justice", and determines the extent to which remedies for breaches of the New Zealand Bill of Rights Act may go beyond those under judicial review.